ON THE RESEARCH OF TERMINOLOGICAL DICTIONARIES (Scientific journal of the Fergana State University, 2024)
The article discusses views on terms and terminology, dictionaries that are the object of lexicography and the principles of their compilation, methodology, types of dictionaries, research on the history of lexicography, as well as the relevance of dictionaries to a certain area of science and technology, discusses terminological dictionaries of the type dedicated to the network, and their types , such as annotated or unannotated and translated. In today's rapidly changing world, the development of industries and the emergence of terms associated with them, as well as the need to form dictionaries related to these areas, indicate the relevance of the topic. In addition, terminological dictionaries related to various fields of science and the authors’ approaches to their formation were analyzed. When forming this article, the method of statistical analysis, the method of structural analysis, the comparative historical method and the comparative descriptive methods were used. The information collected from the study and the findings associated with it are also summarized.